GEDUNG OLAHRAGA BULU TANGKIS DI BANJARMASIN - Agisna, Nur; Saud, Mohammad Ibnu (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
This type of badminton sports building is included in the category of achievement sports. The type of achievement sports is influenced by endogenous factors or within a person (talent), as well as exogenous which means external factors or environmental factors that affect a person. The Badminton Sports Hall in Banjarmasin is a place designed to meet and support the needs of an athlete to channel the skills and talents possessed by individuals or groups. Badminton in Banjarmasin has many fans and is one of the sports that can compete at the national level which causes the government and private parties to provide athlete training. The facilities to support badminton in Banjarmasin are still not optimal, therefore facilities are needed that can better meet these needs. This badminton sports hall is designed according to national standards so that it can be used optimally according to its function. As well as paying attention to the materials used, the required building openings, the orientation of the building, the use of the building envelope, and the arrangement of the outer space on the site.